Emerging trends in physical education and inclusive education: A scientometric analysis - Bjelica, Bojan; Quintero, Armando Monterrosa; Karimi, Amir; Skrypchenko, Iryna; Abdullah, Nagoor Meera (Edu Sportivo: Indonesian Journal of Physical Education, 2024)
Background Problems: In recent years, there has been a growing recognition of the importance of inclusive education and physical education in promoting equality, diversity, and overall well-being among students. However, there is a need for a comprehensive understanding of the scholarly landscape and emerging trends in this field. Research Objectives: The aim of this study is to develop a scientometric analysis of scientific production on inclusive education and physical education. Methods: The databases used in this study were acquired from the Web of Science (WoS) and SCOPUS, with the most recent update occurring in 2021. The bibliographic datasets were pre-processed using ScientoPy and VOSviewer. Findings/Results: The results showed that: (i) The trend of publications related to inclusive and physical education has reached 438 papers since its first publication in 1968. Additionally, it is demonstrated that the distribution of papers increases progressively over time. (ii) Justin A. Haegele of Old Dominion University, Norfolk, United States, has become the most contributing and influential writer in the field of inclusive education and physical education, with 11 papers and 192 citations; Of the 10 journals identified, Physical Education and Sport Pedagogy was the journal that contributed the most with 33 papers; the most influential top paper with 172 citations was entitled “Inclusive physical education from the perspective of students with physical disabilities."  The most frequently used keywords were “physical education," "inclusion,” and “inclusive education." Conclusion: The scientometric analysis revealed a wealth of research on inclusive and physical education for students with disabilities, thereby broadening the scope of adaptive physical education. By emphasising the role of inclusive education in promoting equality, diversity, and overall well-being among students, this research contributes to the ongoing discourse on the establishment of inclusive environments in educational settings.